2012
DOI: 10.1111/j.1365-2125.2012.04284.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in oral drug bioavailability following bariatric surgery: examining the variable extent of impact on exposure of different drug classes

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Changes to oral drug bioavailability have been observed post bariatric surgery. However, the magnitude and the direction of changes have not been assessed systematically to provide insights into the parameters governing the observed trends. Understanding these can help with dose adjustments. WHAT THIS STUDY ADDS • Analysis of drug characteristics based on a biopharmaceutical classification system is not adequate to explain observed trends in altered oral drug bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 100 publications
1
55
0
Order By: Relevance
“…The selected drugs (simvastatin, omeprazole, diclofenac, fluconazole and ciprofloxacin) had a wide range of physicochemical and metabolic attributes and were commonly used in patients undergoing bariatric surgery [12] . Oral drug exposure was simulated for a low, medium and high therapeutic dose in accordance with the British National Formulary, which included: simvastatin immediate release (10, 20 and 80 mg), diclofenac enteric coated (25, 50 and 75 mg), omeprazole enteric coated (10, 20 and 40 mg), fluconazole immediate release (50, 200, 400 mg) and ciprofloxacin immediate release (250, 500 and 750 mg).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected drugs (simvastatin, omeprazole, diclofenac, fluconazole and ciprofloxacin) had a wide range of physicochemical and metabolic attributes and were commonly used in patients undergoing bariatric surgery [12] . Oral drug exposure was simulated for a low, medium and high therapeutic dose in accordance with the British National Formulary, which included: simvastatin immediate release (10, 20 and 80 mg), diclofenac enteric coated (25, 50 and 75 mg), omeprazole enteric coated (10, 20 and 40 mg), fluconazole immediate release (50, 200, 400 mg) and ciprofloxacin immediate release (250, 500 and 750 mg).…”
Section: Methodsmentioning
confidence: 99%
“…Different types of bariatric surgery will impose a number of physiological changes varying in extent depending on the invasiveness of the procedure. Many of these alterations are known to affect the bioavailability of orally administered drugs, although studies investigating alterations in oral drug exposure pre‐ to postoperatively have been limited [12] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SG and AGB are solely restrictive. In SG, a longitudinal resection of the stomach reduces its volume to approximately 60–80 mL, thereby restricting caloric intake 4, 5 . In AGB, an adjustable silicone band is placed around the stomach to create a smaller pouch that similarly restricts caloric intake.…”
Section: Types Of Bariatric Surgerymentioning
confidence: 99%
“…Indeed, a study found that using PK parameters within a biopharmaceutical classification system could not alone explain the observed variability in bioavailability after bariatric surgery 4 . Therefore, the sum of the changes imparted by bariatric procedures makes it difficult, if not impossible, to accurately predict oral bioavailability – and, consequently, PK, clinical efficacy and safety – for a given drug without a dedicated study of that drug 2, 28 .…”
Section: Influence Of Weight and Weight Loss On Pharmacokineticsmentioning
confidence: 99%